SUSTAINABLE FINANCING MODELS FOR RURAL WATER SUPPLY SYSTEMS: A BIBLIOMETRIC REVIEW USING VOSVIEWER - Trimo Pamudji Al Djono Al Djono; M. Benny Alexandri; Anang Muftiadi; Daniel (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Access to safe drinking water is a fundamental component of sustainable development, particularly in rural areas. In Indonesia, the PAMSIMAS program has played a crucial role in expanding such access. However, the program's sustainability heavily depends on the effectiveness and longevity of its financing models. This study adopts a bibliometric approach using VOSviewer software to map global and national research trends related to sustainable financing in rural water supply services from 2014 to 2025. An analysis of 93 publications from the Scopus database reveals that topics such as sustainability, water supply, and community participation dominate, while more specific themes like financial models, subsidies, and public-private partnerships remain underexplored. Identifying these knowledge gaps highlights the need for integration of technical, social, and financial aspects in water financing. The study recommends developing innovative, community-based financing models, engaging stakeholders, and securing policy support from the government. By applying business administration and risk management approaches, this research offers both a conceptual framework and practical recommendations to enhance the sustainability of rural drinking water systems in Indonesia and in a broader global context.